Coriander production under nutrient solution prepared with brackish waters and seeding densities - José A. Santos Júnior; Hans R. Gheyi; Martiliana M. Freire; Marianne de L. Barboza; Laércia da R. F. Lima; Antônio R. Cavalcante (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The use of brackish water in semi-arid regions is sometimes necessary, as water is the most limiting factor for agricultural production in these regions. The present study was conducted aiming to evaluate the production of bunches of Coriandrum sativum L., cultivar Tabocas, in hydroponic system plants exposed to nutrient solutions prepared with brackish water, obtained by mixing water from a community dam (electrical conductivity of 9.93 dS m-1) with rainwater. The treatments consisted of four values of electrical conductivity of the nutrient solution (1.49, 3.14, 4.87, and 6.44 dS m-1) and three seeding densities (1.0, 1.5, and 2.0 g of seeds per cell), arranged in a completely randomized experimental design in a 4 × 3 factorial scheme, with three replicates. Plant height was not affected up to the electrical conductivity of the nutrient solution of 6.44 dS m-1 with increasing seeding density. The electrical conductivity of the nutrient solution up to 6.44 dS m-1 at the seeding density of 2.0 g of seed per cell did not affect the shoot fresh and dry mass of the hydroponic coriander, mitigating the deleterious effect of salinity on water use efficiency.